Stability Analysis of Shield Inclined Tunnel Faces under the Change Effect of Soil Heterogeneity and Pore Water with Buried Depth. (7th July 2022) - Sun, Hong; Zhang, Dao-bing; Yin, Hua-dong; Hu, A-ping
Abstract : The purpose of this work is to look at how soil heterogeneity and pore water pressure impact shield inclined tunnel excavation face stability as burial depth varies. The calculation model of excavation face stability was established, and the supporting pressure of maintain the excavation face stability was solved via the upper bound method. The results showed that the soil heterogeneity coefficient and pore water pressure coefficient had substantial effects on the supporting pressure. The location of failure face and failure range of shield inclined tunnel under varied heterogeneity coefficient and pore water pressure coefficient were presented. In addition, the boundary depth of shallow tunnel under the influence of soil heterogeneity and pore water was obtained, which supplemented the relevant tunnel code.